Development without deforestation - Michael MacLennan; Carlos Ferreira de Abreu Castro; Guilherme B. R. Lambais (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
The conservation projects managed by the United Nations Development Programme (UNDP) in Brazil are underpinned by a strong element of inclusive local development, consisting of innovative initiatives regarding the sustainable use of biodiversity. There are many examples of projects in Mangrove, Caatinga and Cerrado areas, which conciliate the production of goods and environmental services with the generation of jobs, income and an increase in life quality. It is always an enormous challenge to assure opportunities to the most vulnerable populations living in areas characterised by a great expansion of agricultural commodities production and cattle ranching, while respecting people's livelihoods and protecting the environment. [...]
Keywords: 330; Development; Deforestation